Transformative Health Education for Blood Pressure Normalization Using 3-in-1 Therapy - Lam Murni br Sagala; Afnijar Wahyu; Hizkianta Sembiring (CV. AFDIFAL MAJU BERKAH, 2026)
Hypertension is one of the leading non-communicable diseases and a major public health concern worldwide. Community-based health education is essential to improve awareness and promote sustainable self-management of blood pressure. Objective: This community service program aimed to improve community knowledge and encourage blood pressure control through the implementation of 3-in-1 Therapy. Methods: The program was conducted among residents of Suka Mulia Hulu Village using health education, demonstrations, and interactive discussions. The intervention consisted of hypertension exercise, cucumber juice consumption, and warm water foot soaking therapy. Educational leaflets were distributed to reinforce participants’ understanding. Results: The participants showed high enthusiasm and actively engaged in the activities. Following the intervention, community members demonstrated improved understanding of hypertension, its risk factors, prevention strategies, and non-pharmacological management. Participants also expressed their willingness to adopt healthy lifestyles and implement the 3-in-1 Therapy regularly. Conclusion: Transformative health education combined with 3-in-1 Therapy effectively enhanced community knowledge and promoted sustainable self-management practices for blood pressure control, thereby contributing to the prevention of hypertension-related complications and improvement of quality of life.